A Norming Study and Library of 203 Dance Movements. (February 2014) - Christensen, Julia F; Nadal, Marcos; Cela-Conde, Camilo José; Gomila, Antoni
Dance stimuli have been used in experimental studies of (i) how movement is processed in the brain; (ii) how affect is perceived from bodily movement; and (iii) how dance can be a source of aesthetic experience . However, stimulus materials across—and even within—these three domains of research have varied considerably. Thus, integrative conclusions remain elusive. Moreover, concerns have been raised that the movements selected for such stimuli are qualitatively too different from the actual art form dance, potentially introducing noise in the data. We propose a library of dance stimuli which responds to the stimuli requirements and design criteria of these three areas of research, while at the same time respecting a dance art–historical perspective, offering greater ecological validity as compared with previous dance stimulus sets. The stimuli are 5–6 s long video clips, selected from genuine ballet performances. Following a number of coding experiments, the resulting stimulus library comprises 203 ballet dance stimuli coded in (i) 25 qualitative and quantitative movement variables; (ii) affective valence and arousal; and (iii) the aesthetic qualities beauty, liking, and interest. An Excel spreadsheet with these data points accompanies this manuscript, and the stimuli can be obtained from the authors upon request.